Choice substantiation of a folded foundation model via laboratory experiment (Academic journal Industrial Machine Building Civil Engineering, 2019)
The examples of recent developments of foundation thin-walled structures and their applications are presented. It is notedthat the purpose is to develop a method for conducting experimental studies of contact interaction between a folded shellfoundation and a deformed base. The purpose of the laboratory tray research is to determine the optimal characteristics of thesuggested foundation design. The article suggested a method for conducting a laboratory tray experiment to compare the operationof two models of folded shell foundations. The main stages of conducting the scientific experiment have been describedand the basic principles of selecting materials, devices and equipment for carrying out the experiment have been considered.The conduct of the experiment including data recording for each foundation model has been described. As a result,subsidence data for each foundation model have been obtained. The findings have been analyzed; subsidence graphs for eachfoundation design have been built. It is concluded that better distribution of external load to the foundation system elementsis achieved due to the application of a hinged joint of prismatic folds with supporting beams. It has been found that the chosenparameters of the second foundation model complied with the optimized results of the experiment planning and enabledto demonstrate the properties of the foundation system load redistribution better.
Keywords: folded shell foundation; method of conducting an experiment; soil